Altered Gene-Regulatory Function of KDM5C by a Novel Mutation Associated With Autism and Intellectual Disability - Vallianatos, Christina N.; Farrehi, Clara; Friez, Michael J.; Burmeister, Margit; Keegan, Catherine E.; Iwase, Shigeki (Frontiers in Molecular Neuroscience, 2018)
Intellectual disability (ID) affects up to 2% of the population world-wide and often coincides with other neurological conditions such as autism spectrum disorders. Mutations in KDM5C cause Mental Retardation, X-linked, Syndromic, Claes-Jensen type (MRXSCJ, OMIM #300534) and are one of the most common causes of X-linked ID. KDM5C encodes a histone demethylase for di- and tri-methylated histone H3 lysine 4 (H3K4me2/3), chromatin marks which are enriched in transcriptionally-engaged promoter regions. KDM5C regulates gene transcription; however, it remains unknown whether removal of H3K4me is fully responsible for KDM5C-mediated gene regulation. Most mutations functionally tested to date result in reduced enzymatic activity of KDM5C, indicating loss of demethylase function as the primary mechanism underlying MRXSCJ. Here, we report a novel KDM5C mutation, R1115H, identified in individual displaying MRXSCJ-like symptoms. The carrier mother displayed a highly skewed X-inactivation pattern. The KDM5C-R1115H substitution does not have an impact on enzymatic activity nor protein stability. However, when overexpressed in post-mitotic neurons, KDM5C-R1115H failed to fully suppress expression of target genes, while the mutant also affected expression of a distinct set of genes compared to KDM5C-wildtype. These results suggest that KDM5C may have non-enzymatic roles in gene regulation, and alteration of these roles contributes to MRXSCJ in this patient.